Pengaruh Sistem Pengendalian Manajemen Dengan Four Lever’s Of Control Model Terhadap Kinerja Karyawan Di Perusahaan Manufaktur Kota Semarang Dengan Tingkat Kreativitas Sebagai Variabel Mediasi - Karyn Natasha Budianto; Monika Palupi Murniati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study attempts to ascertain the impact of the management control system with the levers of control model, which comprises belief systems, boundary systems, diagnostic systems, and interactive systems on employee performance with a mediating variable, namely the degree of employee creativity. This form of research, which is quantitative, makes use of primary data collected by sending questionnaires to industrial businesses in Semarang, Central Java, through Google Form. 84 firm managers, including top and intermediate managers, participated in the survey as respondents. Based on the probability sampling approach, sampling was computed. Three different multiple linear regression techniques were used in this study to test three different hypotheses: (1) the effects of management control systems on worker productivity; (2) the effects of management control systems on worker creativity; and (3) the effects of management control systems and creativity as mediating factors on worker productivity. The results of this study show that the management control system, which consists of components of the belief system and interaction system, has a substantial impact on improving employee performance and creativity. Employee productivity and creativity are unaffected by this, and neither are the boundary system and diagnostic system characteristics. The creative variable also has the power to limit the management control system's effect on employee performance. Keywords : Belief Systems, Boundary Systems, Interactive Control Systems, Diagnostic Control Systems, and Creativity